2014
DOI: 10.1007/s12291-014-0443-3
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Obesity Associated with Elevated Serum Butyrylcholinesterase Activity, Insulin Resistance and Reduced High Density Lipoprotein-Cholesterol Levels

Abstract: Abdominal obesity (AO) has a strong correlation with cardiovascular disease and has been linked to Alzheimer's disease and type 2 diabetes. We investigated the association between AO and elevated serum butyrylcholinesterase (BChE) activity, insulin resistance and the serum lipid profile, including triglyceride (TG), HDLcholesterol (HDL-C) and LDL-cholesterol (LDL-C) levels in AO and non-AO women subjects. A total of 500 AO subjects (age 49.1 ± 10.5 years), and 142 non-AO women subjects (age 49.9 ± 11.9 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
2
6
0
1
Order By: Relevance
“…The secretion of these mediators alters body weight homoeostasis and contributes to the development of insulin resistance, diabetes and dyslipidemia [51]. The relationship between abdominal obesity and low HDL-C has been demonstrated is several studies [52][53][54][55]. Furthermore, in our study, moderate-to-vigorous physical activity was not associated with HDL-C in the logistic regression models.…”
Section: Discussionsupporting
confidence: 45%
“…The secretion of these mediators alters body weight homoeostasis and contributes to the development of insulin resistance, diabetes and dyslipidemia [51]. The relationship between abdominal obesity and low HDL-C has been demonstrated is several studies [52][53][54][55]. Furthermore, in our study, moderate-to-vigorous physical activity was not associated with HDL-C in the logistic regression models.…”
Section: Discussionsupporting
confidence: 45%
“…revealed that the activity of serum BChE was positively correlated with TC, TG, and LDL-C. This is in agreement with the report ofTangvarasittichai et al (2015). BChE activity was negatively correlated with increasing incorporation of pigeon pea flour in the production of the composite biscuits.…”
supporting
confidence: 92%
“…A potential therapeutic use of BChE is for prevention of nerve agent toxicity (CLSI, 2008;Tangvarasittichai et al, 2015). Figure 3 on the administration of dexamethasone on diabetic rats which significantly diminished the catalytic activities of plasma BChE.…”
Section: Effect Of Composite Biscuits On the Serum Butyrylcholinestmentioning
confidence: 99%
“…Strongly associated with insulin resistance are both psoriasis [ 123 ] and obesity [ 124 ]. In both, there are also common pro-inflammatory pathways involved (TNF-α, IL-6).…”
Section: Introductionmentioning
confidence: 99%